(untitled) (Kinesiology, 2019)
Based on previous research on certain differences among play positions in basketball, differences in aerobic and anaerobic fitness capacity values among basketballers in different playing positions were analyzed. The total sample of 70 adult basketball players (age 24.37±4.05) from the Croatian Division 1 league were classified as point guards (n=20), shooting guards and small forwards (n=26), and power forwards and centers (n=24). A treadmill progressive all-out spiroergometry test was used to find the differences between participants aerobic and anaerobic capacity values. Regarding aerobic abilities, a significant difference between the three playing positions was found only in the VO2max parameters (p<.01) in favor of power forwards and centers (54.8 ml/kg/min ) when compared to point guards, and shooting guards and small forwards (56.7, 55.0 ml/kg/min ). No significant difference was found in the Croatian basketballers’ anaerobic capacity parameters among the three different playing positions.